Seasonal patterns of global oil consumption: Implications for long term energy policy - Inchauspe, Julian; Li, Jun; Park, Jason (2020)
© 2020 The Society for Policy Modeling The dynamic evolution of the seasonal patterns in world oil consumption is dictated by complex interactions between regional consumers. Although this global pattern was stable and predictable in the past, recently it has undergone dramatic changes that have not been well understood yet. This paper contributes to literature on oil consumption behaviours by analysing the counter-balance of ‘coincident’ and ‘counter-directional’ regional seasonal patterns that have time-varying amplitude relative to their longer-term trends. It is shown that the recent global seasonal changes have been mainly driven by long-run demand trends in fast-growing emerging markets and, to a lesser extent, by idiosyncratic changes in regions’ seasonal amplitude. Our analysis is relevant to energy policy in general as both global and regional oil consumption seasonality have important implications for oil pricing, investment decisions, hedging, geopolitics and energy security.